2021
DOI: 10.3390/ijerph18084371
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends of Percutaneous Injuries in Hospital Nurses: Evidence of the Interference between Effects of Adoption of Safety Devices and Organizational Factors

Abstract: Few studies have focused on the combined effects of devices and work organization on needlestick injuries trends. The aim of the study was to estimate trends of percutaneous injury rates (IR) in nurses (N) and nurse assistants (NA) over a 10 year period, in which passive safety devices were progressively adopted. Percutaneous and mucocutaneous injuries registered in a University Hospital in Northern Italy in Ns and NAs in 2007–2016 were analyzed. Organizational data were also available on shift schedules, turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(12 reference statements)
0
3
0
1
Order By: Relevance
“…Other studies of nurses found that night shift work was a risk factor for sharps and needlestick injury (d’Ettorre, 2017; d’Ettorre et al, 2020; Ferrario et al, 2021). We have no evidence, however, that the pattern of night shift work changed at either HC1 or HC2 during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies of nurses found that night shift work was a risk factor for sharps and needlestick injury (d’Ettorre, 2017; d’Ettorre et al, 2020; Ferrario et al, 2021). We have no evidence, however, that the pattern of night shift work changed at either HC1 or HC2 during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…This may be an acceptable hypothesis to explain the downward trend among mid-level professionals. A study that analyzed the temporal trend in the rate of percutaneous injuries in a hospital during the progressive implantation of NS with safety devices to replace conventional NS observed a downward trend among professionals (nurses assistants) who have secondary education ( 31 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo que analisou a tendência temporal da taxa de lesões percutâneas em um hospital durante a implantação progressiva de MP com dispositivos de segurança para substituir MP convencionais observou uma tendência de queda entre profissionais (auxiliares de enfermagem) que possuem ensino médio (31) . A tendência temporal crescente da incidência de acidentes percutâneos entre os trabalhadores com tempo igual ou superior a 61 meses de experiência profissional na instituição hospitalar pode ser explicada pelos fatores comportamentais, como a dificuldade de adesão aos treinamentos (32) e excesso de confiança para realizar procedimentos invasivos (15,28) .…”
Section: Sexounclassified